A Minireview of the Promising Drugs and Vaccines in Pipeline for the Treatment of COVID-19 and Current Update on Clinical Trials - Venkadapathi, Jeyanthi; Govindarajan, Venkat Kumar; Sekaran, Saravanan; Venkatapathy, Santhi (Frontiers in Molecular Biosciences, 2021)
The COVID-19 is affecting thousands of peoples day by day and continues to spread across the world. The present review has focused on promising repurposing drugs, including remdesivir, lopinvar/retinovar, favipiravir, hydroxychloroquine, monoclonal antibodies and vaccines against the SARS-CoV-2 infection. Besides, our review has also focused on many organizations that are in the race to develop vaccines using various approaches including DNA, RNA, viral vectors and subunit proteins against this highly contagious respiratory disease. The spike protein is being studied by scientists all over the world to develop potential vaccines. The antiviral drugs, antibodies and vaccines developed by various researchers around the world have entered clinical trials in humans. The current clinical trials for antiviral agents and vaccines with promising outcomes are being discussed. So far, four vaccines developed by the Pfizer-BioNTech vaccine, the Johnson & Johnson vaccine and two AstraZeneca vaccines (produced by SKBio in the Republic of Korea and Serum Institute of India) are approved by the World Health Organization for public use.